2021
DOI: 10.5271/sjweh.3968
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial work exposures and health outcomes: a meta-review of 72 literature reviews with meta-analysis

Abstract: Psychosocial work exposures and health outcomes: a meta-review of 72 literature reviews with meta-analysis by Niedhammer I, Bertrais S, Witt K This meta-review aimed to present all available pooled estimates for the associations between psychosocial work exposures and health outcomes. Given its very broad objective, it is probably the most comprehensive meta-review performed so far on this topic. Based on a rigorous methodology, this meta-review underlines convincing associations as targets for prevention, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
135
1
10

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 170 publications
(156 citation statements)
references
References 83 publications
10
135
1
10
Order By: Relevance
“…Despite the massive research efforts, as evident by the number of studies published, it seems some disputes remain unchanged. For example, the above-mentioned recent review by Mikkelsen et al reported numerous associations between psychosocial working conditions and risk of depressive disorders ( 25 ), confirming and extending the results of the meta-review ( 1 ). However, due to methodological limitations of the literature, the authors did not feel confident to conclude whether psychosocial working conditions are likely or unlikely to cause depressive disorders.…”
Section: The Past 20 Years Of Researchsupporting
confidence: 59%
See 1 more Smart Citation
“…Despite the massive research efforts, as evident by the number of studies published, it seems some disputes remain unchanged. For example, the above-mentioned recent review by Mikkelsen et al reported numerous associations between psychosocial working conditions and risk of depressive disorders ( 25 ), confirming and extending the results of the meta-review ( 1 ). However, due to methodological limitations of the literature, the authors did not feel confident to conclude whether psychosocial working conditions are likely or unlikely to cause depressive disorders.…”
Section: The Past 20 Years Of Researchsupporting
confidence: 59%
“…This issue of the journal includes a meta-review, ie, a systematic review of systematic reviews, summarizing the published evidence on the associations between exposure to adverse psychosocial working conditions and risk of developing diseases or disorders during the past 20 years ( 1 ). Although the authors allowed inclusion of reviews reporting results from cross-sectional studies, the majority of the included reviews were restricted to prospective cohort studies – the gold standard method in psychosocial occupational epidemiology.…”
mentioning
confidence: 99%
“…PE has been linked to adverse health outcomes such as occupational injuries and poor mental health [ 9 , 10 ]. Psychosocial work environment hazards have been linked with several health outcomes [ 11 ], and it has been suggested that this may be one of the pathways linking PE to adverse health [ 12 , 13 ], but empirical evidence is lacking.…”
Section: Introductionmentioning
confidence: 99%
“…A systematic meta-review has indicated that there may be an association between a negative work environment and the development of work-related stress, depression, and anxiety [ 14 ]. Another recent meta-review of 72 literature reviews also showed a strong association between psychosocial factors with mental disorders, especially with regard to job strain, long working hours, and effort-reward imbalance [ 15 ].…”
Section: Introductionmentioning
confidence: 99%